Destination marketing system design using Rapid Application Development - Yerik Afrianto Singgalen (Jurnal Mantik, 2024)
This research aims to design a destination marketing system capable of accommodating information of product, price, place, and promotion. The method employed is Rapid Application Development (RAD), comprising the phases of requirement planning, user design, construction, and cutover. The outcomes of the study underscore that details regarding product offerings, pricing structures, geographical considerations, and promotional strategies are instrumental for decision-making in optimizing tourist visitation. With its iterative and collaborative nature, the utilization of RAD proves effective in systematically developing a system that aligns with the multifaceted dynamics of destination marketing. The phased approach, from requirement planning to cutover, ensures the systematic incorporation of crucial elements within the system. In conclusion, the research findings emphasize the significance of a well-designed destination marketing system in consolidating and utilizing product, price, place, and promotion information for informed decision-making in the tourism sector